Hypercalcemia in glycogen storage disease type I patients of Turkish origin - Kasapkara, Çiğdem Seher; Tümer, Leyla; Okur, İlyas; Eminoğlu, Tuba; Ezgü, Fatih Süheyl; Hasanoğlu, Alev (The Turkish Journal of Pediatrics, 2012)
Glycogen storage disease type I (GSD I) is an autosomal recessive disorder caused by defects in the glucose-6-phosphatase complex. Deficient activity in the glucose-6-phosphatase-a (G6Pase) catalytic unit characterizes GSD IA and defects in the glucose-6-phosphate transporter protein (G6PC) characterize GSD IB. The main clinical characteristics involve fasting hypoglycemia, hyperuricemia, hyperlactatemia, and hyperlipidemia. Hypercalcemia arose as an unknown problem in GSD I patients, especially in those with insufficient metabolic control. The aim of the present study was to obtain the prevalence of hypercalcemia and to draw attention to the metabolic complications of GSD I patients, including hypercalcemia in poor metabolic control. Hypercalcemia frequency and the affecting factors were studied cross-sectionally in 23 GSD I pediatric subjects. Clinical diagnosis of GSD I was confirmed in all patients either through documentation of deficient G6Pase enzyme activity levels on liver biopsy samples or through G6PC gene sequencing of DNA. Hypercalcemia was detected in 78.3% of patients with GSD I. Different from the previous report about hypercalcemia in a GSD IA patient who had R83H and 341delG mutations, we could not identify any genotype-phenotype correlation in our GSD I patients. Hyperlactatemia and hypertriglyceridemia correlated significantly with hypercalcemia. Furthermore, no differences in serum calcium concentrations could be demonstrated between patients with optimal metabolic control. We observed hypercalcemia in our series of GSD I patients during acute metabolic decompensation. Therefore, we speculate that hypercalcemia should be considered as one of the problems of GSD I patients during acute attacks. It may be related with prolonged lactic acidosis or may be a pseudohypercalcemia due to hyperlipidemia that can be seen in GSD I patients with poor metabolic control.